Creative Concepts of Bessarabian Laureates’ Works in Art Competition of International Academy of Contemporary Arts (Art-Literature-Photography): Array - Shevchuk, Tetyana; Shykyrynska, Olha (Journal of Danubian Studies and Research, 2020)
The article deals with the creative activities of the representatives from Bessarabia (Izmail and Chisinau) in art competition of International Academy of Contemporary Arts in nominations of painting, literature and photography. The author analyzes the creative ideas of art works of the regional representatives, which were highly praised by the jury of the international competition.